Analisis Perancangan Alat Kerja untuk Menghindari Musculoskeletal Disorders Menggunakan Metode Rapid Entire Body Assessment (REBA) di CV Rama Teknik - Fahrudin, Wakhit Ahmad; Candra, Adi; Zulziar, Marjuki (Universitas Pamulang, 2024)
an Research analysis was carried out on designing work tools to avoid musculoskeletal disorders using the Rapid Whole Body Assessment (REBA) method at CV Rama Teknik. Data was collected through asking questions during interviews, and filling out the Nordic Body Map (NBM) questionnaire to ascertain which parts of the body experienced discomfort which could cause a certain level of musculoskeletal disorders. The posture conditions of assembly process workers that can cause musculoskeletal disorders are sitting work posture and standing work posture. The results of the Pick Test observations showed that the frequency of the slouched sitting position was 41 times with a percentage of 46% and the frequency of the upright sitting position was 49 times with a percentage of 54%. The results of the Nordic Body Map questionnaire indicate that the risk level for workers' MSDs is